Influence of the step length and position of the front knee on load conditions of the knee and hip during lunges - Schütz, P.; List, R.; Zemp, R.; Lorenzetti, S. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The aim of this study was to quantify the differences in the loading conditions of the lunge strength exercise at different step lengths and different tibia angles of the front leg. Eleven subjects performed lunges with 25 % body mass (BM) barbell extra load on two force plates. The movement was recorded with a motion capture system. The angles and the forces were calculated using inverse dynamics. A larger tibia angle led to a smaller ROM of the front knee, a larger ROM of the rear knee and hip, whereas a larger step length decreased the ROM of the rear knee and hip. A larger tibia angle resulted in a decreased moment in the front knee, front and rear hip and an increased moment in the rear knee. This possibility for varying the angles and corresponding moments allows coaches and therapists to adapt the lunge to an efficient exercise for strength training.